2018
DOI: 10.1038/s41598-018-29478-4
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal steroid levels in rock pigeon eggs do not represent adequately maternal allocation

Abstract: Maternal hormones deposited in the egg can provide a powerful model for the study of maternal effects. The differential amount of maternal hormones in the yolk of freshly laid eggs is assumed to represent differential maternal allocation. However, some evidence suggests that these amounts do not reflect maternal allocation that in fact takes place before ovulation. We compared the amounts of a wide array of gonadal steroids and their metabolites in the yolk of pre-ovulatory follicles with those of freshly laid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Alternatively, the embryonic activity could have been responsible for activating maternal enzymes in the yolk. However, in another study on rock pigeon we did not find any evidence for presence of maternal enzymes in the yolk (Kumar et al, 2018).…”
Section: Discussioncontrasting
confidence: 67%
“…Alternatively, the embryonic activity could have been responsible for activating maternal enzymes in the yolk. However, in another study on rock pigeon we did not find any evidence for presence of maternal enzymes in the yolk (Kumar et al, 2018).…”
Section: Discussioncontrasting
confidence: 67%
“…In brief, nests were located by visually searching for the bulky nest structure of robins; when located, the contents were examined using a telescopic mirror. Because maternal investment into egg yolks, including yolk hormones, can vary with laying order (e.g., Schwabl 1993 , but see Kumar et al. 2018 ), we aimed to standardize our study by only using nests where the identity of the first laid egg was known for collection and yolk analyses (see below); therefore, we monitored several mid-construction and completed but empty nests prior to the first egg appearing.…”
Section: Methodsmentioning
confidence: 99%
“…as used in [38,62 -64]). Finally, a recent study revealed that maternal hormones are already partly metabolized in the oviduct after ovulation [59]. This provides another hurdle for the interpretation and experimentation with maternal hormones, as levels measured at oviposition may not adequately reflect what the mother initially deposited in the egg.…”
Section: (C) What Is In An Egg? Challenges and Advances In The Measurement Of Yolk Hormonesmentioning
confidence: 99%